The role of knowledge systems in the linguistic construction of action scenes in novels and their translations - Jacobsen, Ronald (HERMES - Journal of Language and Communication in Business, 2005)
What makes one translation better than another? This paper argues that the best is the one that best mirrors the levels of organisation found in the source text while at the same time achieving coherence on as many of them as possible. For instance, in the English translation of Peter Hoeg’s novel Smilla’s Sense of Snow, the original Danish sentence which contains a BE-perfect, Med Esajas i sin kiste er kommet et følge [‘With Isaiah in his cofﬁn is come a procession’] (Høg 1993: 11) is translated as: A procession follows Isaiah in his cofﬁn (Hoeg 1993: 4). This translation may achieve grammatical and local coherence, but certainly not global coherence since it involves a re-construal of the preceding text as a dynamic, or evolving, scene thereby clashing with the static one constructed in the source text. Likewise, it disagrees with the propositional content of the source text on several levels. This may be as it is, but the real problem is: how do you model the relations between the several levels of organisation found in a text like this in order to qualify/support a particular translation? The answer to this problem, this paper argues, is mental space (MS) theory. Accordingly, an outline of a very detailed analysis of the action scene constructed in the beginning of Don DeLillo’s novel Underworld (DeLillo 1999a) is presented and compared with its Danish translation (DeLillo 1999b).